Advancing Masonry Engineering: Effective Prediction of Prism Strength via Machine Learning Techniques - Panumas Saingam; Burachat Chatveera; Adnan Nawaz; Muhammad Hassan Ali; Sandeerah Choudhary; Muhammad Salman; Muhammad Noman; Preeda Chaimahawan; Chisanuphong Suthumma; Qudeer Hussain; Tahir Mehmood; Suniti Suparp; et al. (Buildings, 2026)
Masonry buildings have shaped construction history since about 6500 BCE. They offer durability, strength, and cost effectiveness, especially in developing countries. Yet assessing compressive strength during construction remains challenging due to the constituent materials soil, cement, and stone, complicating standardization worldwide. In the present study, an innovative model based on a machine learning algorithm is put forth to predict the compressive strengths of prisms. Some important factors considered as input to the algorithm based on traditional methods are the brick and mortar strengths, prism geometry, mortar bed thickness, and empirically derived height-to-thickness (t) (h/t) ratios. Three different ANN algorithms are coded and trained on the input data, and they are based on the Levenberg–Marquardt algorithm, the resilient backpropagation algorithm, and the conjugate gradient algorithm. The optimal ANN model trained using the conjugate gradient Polak–Ribière algorithm (traincgp) achieves superior performance, with R2 = 0.9881, R2 = 0.9927, RMSE = 0.9914 MPa, MAE = 0.6039 MPa, MAPE = 20.9141%, VAF = 0.9881, and WI = 0.9970. Sensitivity analysis shows the height-to-thickness (h/t) ratio is the dominant influence on compressive strength, consistent with structural mechanics. The primary contributions are the systematically curated, richly parameterized dataset and its use to produce robust, physically interpretable predictions with established ANN methods.
Keywords: Innovative concrete reinforcement materials; Masonry and Concrete Structural Analysis; Rock Mechanics and Modeling